Representações sociais de coordenação de curso superior de graduação: construindo identidades na educação profissional - Guerch, Cristiane Ambrós (2018)
This dissertation is included in the research line Policies and Management in Professional and Technological Education of the Master's Program in Professional and Technological Education, which seeks to investigate the social representations in positions of coordination of undergraduate courses of the Federal Institute Farroupilha - Campus Júlio de Castilhos from the view of the coordinators themselves. This research will have as theoretical foundation the Theory of Social Representations of Moscovici (1978), besides the contributions of Jodelet (2001), Abric (1998) and Sá (1996), making use of a qualitative research methodology, with case study, using as data construction tools the semistructure interview and the Free Word Association technique. The research subjects were the current Undergraduate Coordinators of the Federal Institute Farroupilha - Júlio de Castilhos Campus. With the understanding of how the Course Coordination is socially represented, this research will contribute to delineate the profile of these professionals who act in the management as coordinators, and, with this, can sensitize them to the qualification of the work with a view to the improvement of the processes of course evaluation and student satisfaction as subjects inserted in the educational process. The results show that social representation is marked in the words "patience", "challenge" and "mobilizer", relevant aspects and that demonstrate that this management position requires profile and availability, positioning itself as a manager that acts in favor of course and Institution, reflecting on the quality and good institutional performance.